Ab initio and experimental study on the mechanism of Al4C3 nitridation in vacuum to prepare AlN. Issue 5 (1st March 2022) - He, Bingyang; Chen, Xiumin; Deng, Pan; Wang, Wenjing; Zhao, Zhongqian; Xu, Youli; Yin, Qi; Xu, Peilin; Liu, Li; Yang, Bin; Liu, Dachun; Xu, Baoqing; et al.
Abstract: Aluminium nitride has good electrical, thermal, and mechanical properties, and Al4 C3 is the most important intermediate in the preparation of AlN through carbothermal reduction. Ab initio molecular dynamics (AIMD) simulations were adopted in this study to elucidate the nitridation reaction mechanism of Al4 C3, and an experimental study was conducted to verify the results of AIMD. Both the AIMD and experimental results showed that the nitridation pathway of Al4 C3 was Al4 C3 →Al5 C3 N→AlN and that the nitridation of Al5 C3 N was considerably rapid. During the nitridation of Al4 C3, the addition of carbon not only had a catalytic effect on the activation of nitrogen molecules but also promoted the aggregation of carbon atoms in the Al4 C3 lattice to form elemental carbon.